Floral ontogeny and anatomy of the shrub Gaiadendron punctatum and a comparison of floral characters in the tribes Gaiadendrinae and Nuytsiae (Loranthaceae) - Suárez, Hernán Darío (2021)
Introducction: Gaiadendron punctatum is a hemiparasitic species of Loranthaceae (Tribe Gaiadendreae) that is widely distributed in mountainous regions of Central and South America. Embryological and phylogenetic studies in the family indicate a trend towards reduction of the gynoecium and ovules, the morphology of which supports the current circumscription of Tribe Gaiadendreae (Gaiadendron and Atkinsonia). Molecular phylogenetic studies suggest that Nuytsia, Atkinsonia and Gaiadendron diverged successively, forming a grade at the base of the Loranthaceae, but support values are low. Objetive: In the present study, the floral anatomy of Gaiadendron punctatum was investigated in order to provide additional data to permit comparisons among the three basal-most genera in the Loranthaceae and reevaluate their relationships. Methods: Flowers of G. punctatum were collected at different developmental stages and serial sections were prepared and analyzed by light microscopy. Results: Inflorescence development is acropetal; the flowers are bisexual with an inferior ovary surmounted by a calyculus, a ring-shaped structure lacking vascular tissue; the ovary is comprised of seven basal locules, each with an ategmic, tenuinucellate ovule. Above the locules is a mamelon that is fused with the adjacent tissues. The androecium is comprised of seven epipetalous stamens, the anthers with fibrous endothecium dehiscence through a single longitudinal slit, releasing tricolpated pollen. Conclusions: The results of this study show that Gaiadendron and Atkinsonia share versatile, dorsifixed anthers, while Gaiadendron and Nuytsia share the same mode of anther dehiscence. On the other hand, Gaiadendron shares with members of Tribe Elytrantheae an amyliferous mamelon and an unvascularized calyculus. Combined phylogenetic analyses of morphological and molecular data are desirable to determine whether Tribe Gaiadendreae comprises a clade, a grade or if the two genera are more distantly related.